Nuclear Factor Erythroid 2 Related Factor 2 Activator JC-5411 Inhibits Atherosclerosis Through Suppression of Inflammation and Regulation of Lipid Metabolism - Jiang, Xinhai; Li, Yining; Wang, Weizhi; Han, Xiaowan; Han, Jiangxue; Chen, Mingzhu; Zhang, Jing; Wang, Chenyin; Li, Shunwang; Luo, Jinque; Wang, Xiao; Xu, Yang; et al. (Frontiers in Pharmacology, 2020)
Phenethyl isothiocyanate (PEITC) is widely present in cruciferous vegetables with multiple biological effects. Here we reported the antiatherogenic effects and the underlying mechanisms of JC-5411 (PEITC formulation) in vitro and in vivo. Luciferase reporter assay showed that JC-5411 increased the activity of nuclear factor erythroid 2-related factor 2 (Nrf2) and antioxidant response element (ARE). JC-5411 treatment significantly increased the protein expression of Nrf2 and its downstream target gene hemeoxygenase 1 (HO-1) in liver of apolipoprotein E deficient (ApoE-/-) mice. Importantly, JC-5411 treatment significantly reduced atherosclerotic plaque area in both en face aorta and aortic sinus when compared with model group in WD induced ApoE-/- mice. JC-5411 obviously decreased proinflammatory factors’ levels in serum of ApoE-/- mice, LPS stimulated macrophages and TNFα induced endothelial cells, respectively. JC-5411 significantly decreased the levels of total cholesterol (TC) and triglyceride (TG) in both serum and liver of ApoE-/- mice and hyperlipidemic golden hamsters. Mechanism studies showed that JC-5411 exerted anti-inflammatory effect through activating Nrf2 signaling and inhibiting NF-κB and NLRP3 inflammasome pathway. JC-5411 exerted regulating lipid metabolism effect through increasing cholesterol transfer proteins (ABCA1 and LDLR) expression, regulating fatty acids synthesis related genes (p-ACC, SCD1 and FAS), and increasing fatty acids β-oxidation (CPT1A) in vivo. Furthermore, JC-5411 treatment had a favorable antioxidant effect in ApoE-/- mice by increasing the antioxidant related genes expression. Taken together, we conclude that JC-5411 as a Nrf2 activator has anti-inflammatory, rebalancing lipid metabolism, and antioxidant effects, which makes it as a potential therapeutic agent against atherosclerosis.